A clinical study on the effect of Mahapasmul decoction on Sthaulya (Overweight and Obesity) - Samarakoon, S.M.S.; Ratnayake, R.M.A.; Herapathdeniya, S.K.M.K. (Indian Journal of Ancient Medicine and Yoga, 2019)
The present study is a clinical study to evaluate the efficacy of Mahapasmul Decoction (MD) on Sthaulya (Overweight and Obesity). Diagnosed patients (30) were selected from Ayurveda Teaching Hospital at Borella, Sri Lanka from the period of January 2015 to May 2016. Patients who had BMI between 25-40 kg/m2 were included in the study. Subjective assessment criteria were the symptoms of obesity with proper grading whereas objective criteria were BMI, body circumferences, skin-fold thickness, lipid profile and FBS. Data were analyzed by using SPSS statistical software. In this study, Mahapasmul Decoction was given for eight weeks, at the dose of 120 ml twice a day, before meals with 5 ml bee honey. Mahapasmul Decoction reduced most of the signs and symptoms of obesity, most of the body circumferences, BMI (from 35.30 ± 0.85 to 32.53 ± 0.92), skin fold thickness, triglyceride (from 122.73 ± 1.68 to 126.45 ± 1.10) and fasting blood sugar (from 95.68 ± 1.67 to 91.91 ± 1.54) in statistically highly significant manner (p<0.001) whereas the improvement of excessive thirst, excessive sweating and drowsiness is significant (p< 0.05). Collectively, MD is composed of katu (20%), tikta (100%) and kasaya rasa (100%); laghu (100%), ruksha (66.6%) and guru guna (16.6%); ushana virya (66.6%); and katu vipaka (100%). The pharmaco dynamic properties of MD reduce kapha and meda and increase agni. Hence, MD is efficacious on promoting digestion and correcting sroto-avarodha. Finally, it is concluded that Mahapasmul Decoction is effective on most of the subjective and objective parameters of Sthaulya (Overweight and Obesity). Keywords: Mahapasmul Decoction; Sthaulya; Obesity; Lipid profile; Fasting blood sugar.
Keywords: Mahapasmul Decoction; Lipid profile; Fasting blood sugar